Challenges faced by women oncologists in Africa: a mixed methods study - Doreen Ramogola-Masire; Reshma Jagsi; Matthew Jalink; Verna Vanderpuye; Nwamaka Lasebikan; Miriam Mutebi; Nazik Hammad; Susan Msadabwe; Laura Carson; Dorothy Chilambe Lombe; Zainab Doleeb; Haimanot Kasahun Alemu; et al. (BMJ Oncology)
Objective Recent studies have identified challenges facing women oncologists in Western contexts. However, similar studies in Africa have yet to be conducted. This study sought to determine the most common and substantial challenges faced by women oncologists in Africa and identify potential solutions.Methods and analysis A panel of 29 women oncologists from 20 African countries was recruited through professional and personal networks. A Delphi consensus process identified challenges faced by women oncologists in Africa, and potential solutions. Following this, focus group discussions were held to discuss the results. Descriptive statistics were used to identify the most common challenges indicated by participants and thematic analysis was conducted on focus group transcripts.Results African women oncologists experienced challenges at individual, interpersonal, institutional and societal levels. The top-ranked challenge identified in the Delphi study was ‘pressure to maintain a work–family balance and meet social obligations’. Some of the challenges identified were similar to those in studies on women oncologists outside of Africa while others were unique to this African demographic. Solutions to improve the experience of women oncologists were identified and discussed, including greater work flexibility and mentorship opportunities.Conclusion Women oncologists in Africa experience many of the challenges that have been previously identified by studies in other regions. These challenges and potential solutions exist at all levels of the social-ecological framework. Women oncologists must be empowered in number and leadership, and gender-sensitive curricula and competencies must be implemented. A systems-level dialogue could bring light to these challenges and foster tangible action and policy-level changes.